Nickel Doping in Atomically Thin Tin Disulfide Nanosheets Enables Highly Efficient CO2 Reduction. Issue 34 (7th August 2018) - Zhang, An; He, Rong; Li, Huiping; Chen, Yijun; Kong, Taoyi; Li, Kan; Ju, Huanxin; Zhu, Junfa; Zhu, Wenguang; Zeng, Jie
Abstract: Engineering electronic properties by elemental doping is a direct strategy to design efficient catalysts towards CO2 electroreduction. Atomically thin SnS2 nanosheets were modified by Ni doping for efficient electroreduction of CO2 . The introduction of Ni into SnS2 nanosheets significantly enhanced the current density and Faradaic efficiency for carbonaceous product relative to pristine SnS2 nanosheets. When the Ni content was 5 atm %, the Ni‐doped SnS2 nanosheets achieved a remarkable Faradaic efficiency of 93 % for carbonaceous product with a current density of 19.6 mA cm −2 at −0.9 V vs. RHE. A mechanistic study revealed that the Ni doping gave rise to a defect level and lowered the work function of SnS2 nanosheets, resulting in the promoted CO2 activation and thus improved performance in CO2 electroreduction. Abstract : Nickel in thin tin : Atomically thin SnS2 nanosheets were modified by Ni doping for efficient electroreduction of CO2 . Introduction of Ni into SnS2 nanosheets enhanced current density and Faradaic efficiency for carbonaceous product relative to pristine SnS2 nanosheets. When the Ni content was 5 at. %, Faradaic efficiency was 93 % with a current density of 19.6 mA cm −2 at −0.9 V vs. RHE.